2015
DOI: 10.1002/jrs.4645
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on SERS of different phase structure TiO2 nanoparticles

Abstract: In this paper, anatase and rutile TiO2 nanoparticles as well as their mixed crystal phase structure TiO2 nanoparticles were synthesized by a sol‐hydrothermal method, and were served as active substrates for surface‐enhanced Raman scattering (SERS) study. The results show that the 4‐mercaptobenzoic acid probe molecules exhibit different degree SERS enhancements on the surface of different phase structure TiO2 nanoparticles. The mixed crystal structure TiO2 with an appropriate proportion of anatase and rutile ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 36 publications
4
40
0
Order By: Relevance
“…. No apparent Raman signal was found from R6G molecule adsorbed on the thin film substrates nitrided at 600 °C, which was consistent with the other literature reported . As the R6G molecules were adsorbed on the thin film substrates nitrided at 700 °C and above temperatures, the characteristic Raman signal of R6G molecule was detected in all the samples, indicating that all the five samples had SERS activity.…”
Section: Resultssupporting
confidence: 90%
“…. No apparent Raman signal was found from R6G molecule adsorbed on the thin film substrates nitrided at 600 °C, which was consistent with the other literature reported . As the R6G molecules were adsorbed on the thin film substrates nitrided at 700 °C and above temperatures, the characteristic Raman signal of R6G molecule was detected in all the samples, indicating that all the five samples had SERS activity.…”
Section: Resultssupporting
confidence: 90%
“…The strongly localized character of the surface plasmon, i.e., its electric field E (r) SP scales with 1/r 3 , limits the probing area down to a few nanometers (d SP ≈ 4-5 nm) [38,39], making the study of the manganite surface by means of Raman spectroscopy in principle possible. However, up to now only a few studies were performed on oxides, mostly focused on nanoparticles rather than thin films [40][41][42]. Moreover, to the best of our knowledge, only one TERS study on a strongly correlated material, the double perovskite La 2 CoMnO 6 [43], was published, but no surface-oriented studies of the mixed-valence manganites, La 1−x A x MnO 3 , were reported up to now.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the mixed crystal structure TiO 2 with an appropriate proportion of anatase and rutile phase is favorable to SERS enhancement of adsorbed molecules. These results are mainly attributed to the contributions of the TiO2‐to‐molecule charge transfer mechanism and the mixed crystal effect . Zhang et al .…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 98%
“…These results are mainly attributed to the contributions of the TiO2-to-molecule charge transfer mechanism and the mixed crystal effect. [19] Zhang et al studied the size-dependent evolution of phonon confinement in colloidal Si nanoparticles using SERS. By introducing a variable confinement factor, α, into a well-known phenomenological phonon confinement model (PCM) developed by Richter et al, acceptable fits were achieved to downshifted and asymmetrically broadened Raman spectra of Si NPs with different diameters.…”
Section: Sers Substratesmentioning
confidence: 99%